The Effect of Yoga Nidra on Academic Stress and Sleep Quality in University Students - Qadir, Harshna Richard; Attri, Arti; Ibrahim, Ahamed Mohamed (Journal of Educational Research and Policies, 2025)
Background: Yoga Nidra is a pratyahara technique originating from Nyasa that induces a deep sleep state, leading to stress management, improvement in sleep quality, and other cognitive functions such as attention, memory, and emotional regulation. Several studies have also shown the effectiveness of Yoga Nidra in coping with psycho - somatic diseases and also providing tranquility of mind. Aim: To investigate the effect of yoga nidra on university students' academic stress and sleep quality. Methodology: The present study was conducted on 26 university students belonging to both male and female gender based on a single group pre - post design. The subjects followed a thirty - minute session of Yoga Nidra five days a week for one month. This study examines academic stress and sleep quality using the Academic Stress Scale and Pittsburgh sleep quality index at the baseline, followed by post - data. Results: This study includes 26 subjects in the pre - and post - study groups for the analysis. It observed a significant reduction in academic stress among university students with a p ≤ 0.04. Improvement in sleep quality was observed after one month of practice of Yoga Nidra with p ≤ 0.01. Conclusion: This study concluded that one month's practice of yoga nidra has been proven beneficial in reducing academic stress and improving the sleep quality of university students.